1981
DOI: 10.1103/physrevd.23.604
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the continuum of dimuons produced in high-energy proton-nucleus collisions

Abstract: We report final results of a series of measurements of continuum dimuon production in proton-nucleus collisions at Femilab. New results with 6 times more statistics are included. A full description of the apparatus and methods used in the analysis of this series of measurements is given. The sea quark distribution of the nucleon is determined within the context of Drell-Yan and quantum-chromodynamic descriptions of dilepton production in hadron collisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
139
0

Year Published

1981
1981
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(142 citation statements)
references
References 62 publications
3
139
0
Order By: Relevance
“…[56,57,77,78]. We used data sets from the E288 experiment [79] [80], extracted from the collision of a proton beam with an energy of 800 GeV ( √ s = 38.8 GeV) on a copper fixed target. The explored Q values are higher compared to the SIDIS case, as can be seen in table 3.…”
Section: Low-energy Drell-yan Datamentioning
confidence: 99%
See 1 more Smart Citation
“…[56,57,77,78]. We used data sets from the E288 experiment [79] [80], extracted from the collision of a proton beam with an energy of 800 GeV ( √ s = 38.8 GeV) on a copper fixed target. The explored Q values are higher compared to the SIDIS case, as can be seen in table 3.…”
Section: Low-energy Drell-yan Datamentioning
confidence: 99%
“…As suggested in ref. [79], we consider the target nuclei as an incoherent ensemble composed 40% by protons and 60% by neutrons.…”
Section: Low-energy Drell-yan Datamentioning
confidence: 99%
“…2) (top), (6.5) (middle), (6.12) (bottom) at NNLO. Here, the kinematics bin-integration, etc., is for Drell-Yan process measured at E288 experiment at E beam = 200GeV and Q = 6 − 7GeV [45].…”
Section: The Tmd Cross-sections Using the Optimal Tmd Distributionsmentioning
confidence: 99%
“…While there were indications ofd =ū from Drell-Yan data in the early 1980's [47] it was observation of a violation of the Gottfried Sum Rule [48] in muon DIS by the New Muon Collaborations [49,50] that forced this belief to be reconsidered. Because of its sensitivity to the antiquark distributions Ellis and Stirling suggested [51] using Drell-Yan as a probe of the light quark flavor asymmetry with hydrogen and deuterium targets.…”
Section: Isospin Symmetry Of the Light Quark Seamentioning
confidence: 99%
“…In these models, virtual pion contributions to nuclear structure functions were expected to lead to sizable increases in sea distributions of the nuclei compared with deuterium [75,76,77]. Early Drell-Yan studies at both CERN [78,79] and Fermilab [47] lacked the statistical sensitivity to observe the expected effects. In 1990, measurements by Fermilab E772 [54] found that the expected enhancement was [54].…”
Section: Antiquark Distributions Of Nucleimentioning
confidence: 99%